Molecular, Circuit, and Stress Response Characterization of Ventral Pallidum Npas1-Neurons - Morais-Silva, Gessynger [UNESP]; Campbell, Rianne R.; Nam, Hyungwoo; Basu, Mahashweta; Pagliusi, Marco; Fox, Megan E.; Chan, C. Savio; Iñiguez, Sergio D.; Ament, Seth; Cramer, Nathan; Marin, Marcelo Tadeu [UNESP]; Lobo, Mary Kay (Society for Neuroscience, 2023)
Altered activity of the ventral pallidum (VP) underlies disrupted motivation in stress and drug exposure. The VP is a very heterogeneous structure composed of many neuron types with distinct physiological properties and projections. Neuronal PAS 1-positive (Npas11) VP neurons are thought to send projections to brain regions critical for motivational behavior. While Npas11 neurons have been characterized in the globus pallidus external, there is limited information on these neurons in the VP. To address this limitation, we evaluated the projection targets of the VP Npas11 neurons and performed RNA-sequencing on ribosome-associated mRNA from VP Npas11 neurons to determine their molecular identity. Finally, we used a chemogenetic approach to manipulate VP Npas11 neurons during social defeat stress (SDS) and behavioral tasks related to anxiety and motivation in Npas1-Cre mice. We used a similar approach in females using the chronic witness defeat stress (CWDS). We identified VP Npas11 projections to the nucleus accumbens, ventral tegmental area, medial and lateral habenula, lateral hypothalamus, thalamus, medial and lateral septum, and periaqueductal gray area. VP Npas11 neurons displayed distinct translatome representing distinct biological processes. Chemogenetic activation of hM3D(Gq) receptors in VP Npas11 neurons increased susceptibility to a subthreshold SDS and anxiety-like behavior in the elevated plus maze and open field while the activation of hM4D(Gi) receptors in VP Npas11 neurons enhanced resilience to chronic SDS and CWDS. Thus, the activity of VP Npas11 neurons modulates susceptibility to social stressors and anxiety-like behavior. Our studies provide new information on VP Npas11 neuron circuitry, molecular identity, and their role in stress response.
Keywords: depression; DREAADs; Npas1; social defeat stress; ventral pallidum